KEBUTUHAN BAHAN BAKU KAYU PADA INDUSTRI PENGOLAHAN KAYU FURNITUR (Studi Kasus PT. Rimba Mutiara Kusuma-Tanggerang) - Pusvitasari, Tia; Susdiyanti, Tun; Lidiawati, Ina (Universitas Nusa Bangsa, 2019)
Sustainability of wood supply is one of the important factors affecting the sustainability of the forestry industry that uses wood as its raw material. This study aims to determine how to manner supply the raw material needs as well as analyze the needs of the wood raw material and purchasing optimal wood raw material in PT Rimba Mutiara Kusuma. The method used in the research of interviews and observations where data are analyzed by qualitative and needs wood raw material by regression analysis